CAMP21-SYNERGIZING LITERACIES: UNVEILING THE NEW HORIZON FOR ENGLISH ENRICHMENT PROGRAM - Mohd Ariff Nafizi Ibrahim; Dr. Shahiza Ahmad Zainuddin; Munawira Saharani (Journal of Islamic, Social, Economics and Development, 2024)
This paper outlines the engagement of CAMP21-Synergizing Literacies (CAMP21) by Jabatan Pendidikan Politeknik dan Kolej Komuniti or JPPKK (Department of Polytechnics and Community Colleges Education) as one of the English enrichment programmes aimed at elevating the language proficiency among students of Polytecnics and Community Colleges in Malaysia. Despite the primary focus of polytechnics and community colleges education on technical and practical learning, the importance of English as an added value to their graduates is acknowledged. Both institutions have developed various English enrichments initiatives to address proficiency challenges faced by their students. In recognizing the significance of English proficiency, these institutions also share their commitment to cultivating their graduates with robust entrepreneurial skills that are enhanced by design thinking methodology. This holistic approach empowers the students of both institutions to comprehend and effectively respond to evolving shifts in their surroundings and behaviours. In response to this objective, JPPKK has formulated CAMP21-Synergizing Literacies (CAMP21), an enrichment module not only introduces students to the design thinking process but also enhances their proficiency in English. By utilizing CAMP21 as a strategic component to attain its Key Performance Indicators (KPIs), JPPKK demonstrates a favourable acceptance pattern that encourages the students from Polytechnics and Community Colleges to embrace this enrichment module. It holds the potential to be adopted by both institutions to foster their students into future graduates who are equipped with advanced design thinking skills and elevated English communication capabilities.